2015
DOI: 10.1111/hdi.12271
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and psychosocial factors predicting health‐related quality of life in hemodialysis patients

Abstract: Many patients with end-stage renal disease have significant impairment in health-related quality of life (HRQoL). Most previous studies have focused on clinical factors; however, quality of life can also be affected by psychosocial factors. The aim of this study was to identify the possible predictors of HRQoL among clinical and psychosocial factors in hemodialysis (HD) patients. The study included 101 patients who were undergoing HD. Psychosocial factors were evaluated using the Hospital Anxiety and Depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 52 publications
5
26
1
2
Order By: Relevance
“…Impaired health‐related quality of life (HRQOL) is associated with mortality in end stage renal disease, yet little is known about the ability of reported symptom or health status to prognosticate in this population. This is despite the reported association between self‐rated health and mortality both in the general population and in chronic kidney disease (CKD) …”
Section: Introductionmentioning
confidence: 99%
“…Impaired health‐related quality of life (HRQOL) is associated with mortality in end stage renal disease, yet little is known about the ability of reported symptom or health status to prognosticate in this population. This is despite the reported association between self‐rated health and mortality both in the general population and in chronic kidney disease (CKD) …”
Section: Introductionmentioning
confidence: 99%
“…One study involving Japanese patients on haemodialysis showed the EQ‐5D score was 0.75 ± 0.17 (Katayama et al, ). Another study among Korean patients on haemodialysis reported the HRQOL was 0.704 ± 0.199 (Kang et al, ). Sakthong & Kasemsup () reported that the EQ‐5D score for patients on peritoneal dialysis in Taiwan was 0.65 ± 0.23, whereas the score for this group in our study was 0.86 ± 0.12.…”
Section: Discussionmentioning
confidence: 99%
“…That study showed that factors such as no spouse, complications and a low education level were associated with lower HRQOL. A South Korean study that evaluated HRQOL among patients on haemodialysis using the EuroQol‐five dimensions (EQ‐5D) indicated that HRQOL deterioration was associated with increased age, increased anxiety and a lack of support from friends (Kang et al, ). The effects of disease on HRQOL are known to vary by differences in social status, cultural heritage, religion and lifestyle (Rui et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported different results regarding the effect of depression on QoL in patients receiving hemodialysis, with some claiming it to be a significant predictor of QoL (Birmele et al, ; Kring & Crane, ; Lee et al, ), and others pointing to its insignificance (Kang et al, ). In this study, the direct effect of depression on QoL was not found to be significant; however, depression was found to have a significant indirect effect on QoL through fatigue as a mediating variable.…”
Section: Discussionmentioning
confidence: 99%